2007
DOI: 10.1111/j.1398-9995.2007.01420.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pollen and nasal glucocorticoid on FOXP3+, GATA‐3+ and T‐bet+ cells in allergic rhinitis

Abstract: These data suggest that nasal glucocorticoids attenuate the allergic inflammation partly by reducing the number of T(H)2 cells, but not by means of local upregulation of Treg cells. The local relationship between T(H)1 and T(H)2 cells as well as between Treg and T(H)2 is maintained by nasal glucocorticoid treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 29 publications
5
38
1
2
Order By: Relevance
“…GC inhibits histamine release from basophils [48,49], induces apoptosis of eosinophils [50] and reduces the recruitment of antigen-presenting cells such as Langerhans cells [51]. GC decreases the numbers of GATA-3 + Th2 cells and the production of Th2 cytokines, such as IL-4, IL-5, IL-6 and IL-13, while having little effect on T-bet + Th1 cells and the production of Th1 cytokines such as IL-2, IL-12 and interferon (IFN)-g [52,53]. Although the inhibitory effect of GC on B cell recruitment is limited, GC inhibits class-switching to IgE in the nasal mucosa [51,54].…”
Section: Cellular Level (Fig 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…GC inhibits histamine release from basophils [48,49], induces apoptosis of eosinophils [50] and reduces the recruitment of antigen-presenting cells such as Langerhans cells [51]. GC decreases the numbers of GATA-3 + Th2 cells and the production of Th2 cytokines, such as IL-4, IL-5, IL-6 and IL-13, while having little effect on T-bet + Th1 cells and the production of Th1 cytokines such as IL-2, IL-12 and interferon (IFN)-g [52,53]. Although the inhibitory effect of GC on B cell recruitment is limited, GC inhibits class-switching to IgE in the nasal mucosa [51,54].…”
Section: Cellular Level (Fig 2)mentioning
confidence: 99%
“…The ratio of FoxP3 + /GATA binding protein 3 (GATA-3 + ) cells in nasal mucosa was decreased significantly in patients with pollinosis as compared with healthy controls outside the pollen season, and the ratio was decreased further during the pollen season in allergic patients [53]. In addition, Tregs are induced in both peripheral blood and nasal mucosa following allergen-specific immunotherapy [68,69].…”
Section: Cd25mentioning
confidence: 99%
“…These findings suggest that T-bet may be a negative regulator in allergic airway inflammation and airway hyperreactivity in both human beings and mice. Malmhäll et al [17] showed that similar levels of T-bet are present in the nasal mucosa in patients with AR and healthy controls, before and during the pollen season. However, a significant decrease in the T-bet + /GATA-3 + ratio was determined during the pollen season.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with AR, Malmhäll et al [17] demonstrated a higher number of FOXP3 + and GATA-3 + cells, but not T-bet + cells, in the nasal mucosa compared with that of healthy subjects before the start of the pollen season. Although, the number of FOXP3 + cells in the nasal mucosa remained the same in AR patients after the pollen season, it decreased significantly following treatment with fluticasone propionate.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46] Analysis of transcription factor expression by using immunohistochemical techniques conflict with some studies that demonstrated FoxP3, T-box transcription factor (T-bet), and TGF-␤ expression to be lower in patients with AR than in controls with increased GATA-3 expression, 47,48 whereas another study found that FoxP3 and GATA-3 have elevated expression in patients with AR, at least during the preallergy season. 49 These discrepancies further highlighted the importance of investigating the functional fitness of Tregs to more accurately denote the functional significance of Treg infiltrates locally within tissues.…”
Section: Alterations In Treg Numbers and Functions In Ar And Crswnpmentioning
confidence: 99%